The values in students of secondary with and without participation in violent acts of Lima Metropolitan - Velásquez Centeno, Carlos (2004)
OBJECTIVE: To know and to describe the values of greater importance in students of secondary of Educative Centers of Lima Metropolitan, as well as the differences in the Values between students who participate and do not participate in violent acts. DESIGN: Corelational descriptive study, in students of the third a fifth of secondary of National Educative Centers of Lima Metropolitan. MATERIAL And METHODS: The sample was constituted by 1226 students with an age average of 16 years. For the construction of the instrument of values the Questionnaire of Values of Valdez J. was had like reference, which was reconstructed and adapted for our reality. RESULTS: One was that the values that govern the life of the students of secondary of Lima Metropolitan are: social adhesion, ethical moral, altruism, monk, civic norms, personal and affiliation development. In the students who do not participate in violent acts predominate the values of social adhesion, ethical-moral, altruism, monk, civic norms and personal development in comparison with the violent ones, whereas the affiliation value is common in both. The women orient themselves by the values of social adhesion, ethical moral, altruism, monk, civic norms and affiliation in comparison with the men, whereas the value is common in both personal development. CONCLUSIONS: According to the single level of training differences in the value exist altruism, determining this that conforms increases the level of training increases to the capacity of loosening and aid to the others. As far as the single age one was differences in the moral ethical value, which indicates to us that in agreement it increases the age consolidate the tie aspects with the autocensoring and the self-acceptance related to the familiar structure.